Pengaruh Konsumsi Sereal Terhadap Perubahan Kadar Hemoglobin Pada Ibu Hamil Anemia Di Wilayah Kerja Puskesmas Sukorame Kota Kediri Tahun 2016 - Galuh Pradian; Fiki Cahya Ningrum (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2017)
anemiapregnant is a major cause of morbidity and mortality in the fetus and infant. The prevalence of anemia pregnant in PuskesmasSukorame still very high, on March-April 2016, there were 117 pregnant, as many as 33 people with a percentage of 38,6% of pregnant women suffer from anemia. The main cause of anemia among pregnant in Indonesia is a deficiency of iron, so that the government implement a program providing iron tablets one tablet per day for 90 days. The purpose of research to prove the effect of the consumption of cereals to changes in hemoglobin levels in anemic pregnant in Puskesmas Sukorame Kediri 2016.This study using Inferential with this type of Preeksperiment research, with pretest posttest design. The population are  33 people, while are 15 people taken at random.Based on statistical test mean Hb level of 9,4 g / dl, the standard deviation of 0.821 and the standard error was obtained 0,212 there as after intervention mean hemoglobin concentration of 10.4 g / dl, the standard deviation of 1,156 and 0,298 standard error of the data it can be seen an average increase in hemoglobin was 0,96 g / dl.Analysis of data obtained using Paired Samples Test 0.000 p value of <0.05, meaning there is the effect of consumption of cereals to changes in hemoglobin levels in anemic pregnant in Puskesmas Sukorame Kediri 2015.One of the nutritiontsthat containt of vitamin C and iron are cereals. Pregnant should consume iron tablet anemia accompanied consume nutritionts that contain of vitamin C and iron because its can help the nutritionts iron  of anemic pregnant. Keywords: Cereals, Tablet Fe, Pregnant, Anemia.